Changes in the Hardness of Aluminum Alloys in the Influence of Lithium - Tursunbaev Sarvar; Turakhodjayev Nodir; Mardanokulov Sharofuddin (Genius Journals, 2022)
In the manufacture of cast parts from aluminum alloys, the hardness of the alloy is important. The article examines the change in their hardness by the Rockwell method when using lithium-fluorine containing compounds from aluminum alloys of grades AK7 and D16 as a flux. The research was carried out in the laboratory of “Foundry technologies” Tashkent State Technical University. Based on the results of the study, the authors draw their conclusions set out in the article
Keywords: hardness; Rockwell; temperature; aluminum